2020
DOI: 10.1186/s12879-019-4742-4
|View full text |Cite
|
Sign up to set email alerts
|

Gaps between current clinical practice and evidence-based guidelines for treatment and care of older patients with Community Acquired Pneumonia: a descriptive cross-sectional study

Abstract: Background: Community acquired pneumonia (CAP) remains a significant cause of morbidity and in-hospital mortality, and readmission rates are rising for older persons (> 65 years). Optimized treatment and nursing care will benefit patients and the health economy. Hence, there is a need to describe gaps between current clinical practice and recommendations in evidence-based guidelines for diagnostic procedures, medical treatment and nursing interventions for older patients with CAP. Methods: Structured observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Some studies revealed possible barriers and challenges for poor adherence of healthcare professionals to treatment guideline. 35 Models were developed to suggest that physicians fail to adhere to guidelines in the presence of an internal barrier that a cognitive (awareness or knowledge) or affective (attitude or motivation) component, or in the presence of an external barrier (patient, guideline and environmental factors) that restricts the professionals’ ability. 36–38 Implementation science indicates that factors determining healthcare professionals (HPs’) adherence to treatment guideline can be linked to both individual, team and organizational level and are related to the context where the treatment and care is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed possible barriers and challenges for poor adherence of healthcare professionals to treatment guideline. 35 Models were developed to suggest that physicians fail to adhere to guidelines in the presence of an internal barrier that a cognitive (awareness or knowledge) or affective (attitude or motivation) component, or in the presence of an external barrier (patient, guideline and environmental factors) that restricts the professionals’ ability. 36–38 Implementation science indicates that factors determining healthcare professionals (HPs’) adherence to treatment guideline can be linked to both individual, team and organizational level and are related to the context where the treatment and care is performed.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance awareness of the phenomenon under study, she expanded her preunderstanding by studying literature about EBGs recommendations for CAP [e.g. 10,11] and barriers and facilitators for HPs' adherence to EBGs [3,6]. The Theoretical Domain Framework (TDF) [26] (14 domains selected from 33 behaviour change theories and 128 constructs) was central in this process as it captures barriers and facilitators for HPs behaviour at individual, team, and organizational levels.…”
Section: Designmentioning
confidence: 99%
“…A group of patients who appear to be deprived of nursing care (NC) interventions according to EBGs are older patients with CAP [2,3,6], leading to fatal patient outcomes. CAP is an acute in ammatory lung disease and a signi cant cause of morbidity and mortality among older persons (>65 years) [7], thus representing a major cost and capacity challenge for hospitals and society [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations